Information search and information distortion in the diagnosis of an ambiguous presentation - Olga Kostopoulou; Christos Mousoulis; Brendan Delaney (Judgment and Decision Making, 2009)
Physicians often encounter diagnostic problems with ambiguous and conflicting features. What are they likely to do in such situations? We presented a diagnostic scenario to 84 family physicians and traced their information gathering, diagnoses and management. The scenario contained an ambiguous feature, while the other features supported either a cardiac or a musculoskeletal diagnosis. Due to the risk of death, the cardiac diagnosis should be considered and managed appropriately. Forty-seven participants (56%) gave only a musculoskeletal diagnosis and 45 of them managed the patient inappropriately (sent him home with painkillers). They elicited less information and spent less time on the scenario than those who diagnosed a cardiac cause. No feedback was provided to participants. Stimulated recall with 52 of the physicians revealed differences in the way that the same information was interpreted as a function of the final diagnosis. The musculoskeletal group denigrated important cues, making them coherent with their representation of a pulled muscle, whilst the cardiac group saw them as evidence for a cardiac problem. Most physicians indicated that they were fairly or very certain about their diagnosis. The observed behaviours can be described as coherence-based reasoning, whereby an emerging judgment influences the evaluation of incoming information, so that confident judgments can be achieved even with ambiguous, uncertain and conflicting information. The role of coherence-based reasoning in medical diagnosis and diagnostic error needs to be systematically examined.